Are Surgical Guideline Changes in Diverticulitis Care Associated With Decreased Inpatient Healthcare Expenditure?. Issue 3 (3rd September 2021) - Lin, Saunders; Dewey, Elizabeth N.; Tsikitis, V. Liana
Abstract : Objective: To examine possible associations in inpatient healthcare expenditure and guideline changes in the surgical management of diverticulitis, in terms of both cost per discharge and total aggregate costs of care. Background: Medical costs throughout the healthcare system continue to rise due to increased prices for services, increased quantities of high-priced technologies, and an increase in the amount of overall services. Methods: We used a retrospective case-control design using the Healthcare Cost and Utilization Project National Inpatient Sample to evaluate cost per discharge and total aggregate costs of diverticulitis management between 2004 and 2015. The year 2010 was selected as the transition between the pre and postguideline implementation period. Results: The sample consisted of 450, 122 unweighted (2, 227, 765 weighted) inpatient discharges for diverticulitis. Before the implementation period, inpatient costs per discharge increased 1.13% in 2015 dollars (95% confidence intervals [CI] 0.76% to 1.49%) per quarter. In the postimplementation period, the costs per discharge decreased 0.27% (95% CI –0.39% to –0.15%) per quarter. In aggregate, costs of care for diverticulitis increased 0.61% (95% CI 0.28% to 0.95%) per quarter prior to the guideline change, and decreased 0.52% (95% CI –0.87% to –0.17) following the guideline change. Conclusions: This is the first study to investigate any associations between evidence-based guidelines meant to decrease surgical utilization and inpatient healthcare costs. Decreased inpatient costs of diverticulitis management may be associated with guideline changes to reduce surgical intervention for diverticulitis, both in regards to cost per discharge and aggregate costs of care. Abstract : Mini-abstract: We performed a retrospective case-control design using the Healthcare Cost and Utilization Project National Inpatient Sample to evaluate costs of diverticulitis management. Decreased inpatient costs of diverticulitis management may be associated with guideline changes to reduce surgical intervention for diverticulitis, both in regards to cost per discharge and aggregate costs of care. Supplemental Digital Content is available in the text.